Effects of WSSV and ammonia nitrogen stress on the enzyme activity and transcriptome of Litopenaeus vannamei - Shan Gao; Linxin Dai; Yue Wang; Zuluan Liang; Yinhuan Zhou; Chengbo Sun (Aquaculture Reports)
White spot syndrome virus (WSSV) is an important pathogen in the aquaculture industry that poses a serious threat to the shrimp farming industry. In this study, Litopenaeus vannamei was selected as the research object to determine the critical concentration of ammonia nitrogen that triggered the outbreak of WSSV. Multiomics techniques were used to study the comprehensive reaction mechanism of L. vannamei, which is in a state of WSSV infection and transforms into acute infection under conditions of ammonia nitrogen stress, from physiological, biochemical, and transcriptomic perspectives. The toxicity of ammonia nitrogen and WSSV to L. vannamei was measured by the LC50 test, and semilethal concentrations at 72 hpi, 96 hpi, 120 hpi, and 144 hpi were obtained. H&E staining revealed pathological changes in the intestinal tract induced by WSSV infection, ammonia nitrogen stress, and combined ammonia nitrogen and WSSV stress in L. vannamei. KEGG pathway enrichment analysis of the DEGs revealed that activation of the PI3K-Akt-mTOR signaling pathway triggers metabolic reprogramming of cells, which is conducive to the WSSV-induced Warburg effect and proliferation. Blocking the PI3K-Akt signaling pathway could reduce the apoptosis of WSSV-infected cells, thereby inhibiting viral replication. Notably, ammonia nitrogen stress disrupted the balance between shrimp and WSSV latent infection, increased the susceptibility to WSSV infection, and aggravated the severity of infection. The obstruction of ammonia metabolism leads to an increase in ammonia nitrogen levels, aggravates the inflammatory response and oxidative stress of the host, causes intracellular oxidative damage and host tissue damage, weakens the immune function of the host, and cannot effectively resist WSSV infection, leading to the acceleration of WSSV replication and disease outbreaks.